Synthesis and research of polyfunctional silicon-containing amines – new promoters of adhesion - K. Yu. Ivanova; M. V. Kuzmin; N. I. Kol’tsov (Chimica Techno Acta)
Currently, in order to obtain high-tech hybrid products, modern adhesives have high requirements for creating strong joints between dissimilar materials. It is known that adhesion depends on the compatibility of the adhesives with the surfaces of the materials. Amine compounds are the main hardeners for epoxy compositions. That is why, in this article, we synthesized silicon-containing amines based on polyfunctional aminoalkoxysiloxanes for epoxy compositions. Aminoalkoxysiloxanes were prepared by the interaction of 3-aminopropyltriethoxysilane with monoethanolamine in nitrogen at atmospheric pressure in the presence of a binary antioxidant and catalytic amounts of an alkali metal alcoholate. During the reaction in a homogeneous phase, the reaction mixture was heated to a temperature of 100-110 °C and distilled off to 90% of ethanol from the theoretically calculated amount. Further, the reaction was carried out at a reduced temperature of 10-20 mmHg pressure until the release of alcohol stops. At the same time, gravimetric control was carried out and the refractive index of the reaction mixture was measured. As a result, aminoalkoxysilanes were obtained in the form of light-yellow oily liquids. The structure of the obtained compounds was investigated by IR spectroscopy on an FSM-1202 Fourier spectrophotometer and 1H NMR spectroscopy on a high-resolution BrukerWM-250 NMR spectrometer. It was found that under the selected synthesis conditions, aminopropyltri-(2-aminoethoxy)silane is obtained with the highest yield of 97.6% at a molar ratio of 3-aminopropyltriethoxysilane AGM-9 with monoethanolamine 1:3.